On the autonomy of the banco de la repúblican (1997)
Temporal inconsistency arguments do not support Central Bank independence advantages when real effects lag behind monetary measures, allowing economic agents to prepare for them. Inflation trend in Colombia is declining at a constant annual rate from 1992, when imports and external price competition begun. Two sudden and drastic changes in monetary policies compromised growth and employment, but could not modify that inflation trend. Exclusive attention to money growth or to interest rate level have induced an increasing volatility in exchange rates. Short term returns to foreign capital investment remain attractive in average, but their very high and increasing volatility can induce speculative capital movements.